Organizational assessment methodology of corporate universities - Matos, Clarissa Leite Braga e; Forte, Sergio Henrique Arruda Cavalcante; Forte, Sérgio Alexandre Barreira (Revista de Administração da UFSM, 2020)
Purpose – In the available literature, we can find research on how to conduct an assessment of an organization’s Corporate Education, but not of the Corporate University. Therefore, in our research we propose a methodology to evaluate the organizational management of Corporate Universities. Design/methodology/approach – This research is descriptive and uses the multicriteria analysis method as basis. Specifically, we use the Multi-Attribute Global Inference of Quality (Magiq) methodology for the definition of weights, to measure the importance of factors and sub-factors that determine the organizational evaluation of Corporate Universities. Findings – The resulting methodology contemplates six factors and 18 sub-factors. The six factors in descending order of weights are: Strategic Management, Organizational Learning, Process, Performance, Institutional and Market. Research limitations/implications – The fact that our research is based on the knowledge of Brazilian experts, it infers the use of this methodology only for the case Brazil, which can be seen as a limitation of this research. Practical implications – The leaders of Corporate Universities will henceforth be able to mirror and look for greater performance to achieve their goals. Originality/value – Our research intends to contribute to reduce the gap either in theory and practice of how to evaluate Corporate Universities. From there, we hope to make possible to compare them, to create rankings and to establish awards, since the existing literature provides criteria on how to evaluate Corporate Education, but not Corporate Universities.